Failure of apoptosis-inducing factor to act as neuroglobin reductase - Moschetti, Tommaso; Giuffrè, Alessandro; Ardiccioni, Chiara; Vallone, Beatrice; Modjtahedi, Nazanine; Kroemer, Guido; Brunori, Maurizio (Biochemical and biophysical research communications, 2009)
Neuroglobin (Ngb) is a hexacoordinate globin expressed in the nervous system of vertebrates, where it protects neurons against hypoxia. Ferrous Ngb has been proposed to favor cell survival by scavenging NO and/or reducing cytochrome c released into the cytosol during hypoxic stress. Both catalytic functions require an as yet unidentified Ngb-reductase activity. Such an activity was detected both in tissue homogenates of human brain and liver and in Escherichia coli extracts. Since NADH:flavorubredoxin oxidoreductase from E. coli, that was shown to reduce ferric Ngb, shares sequence similarity with the human apoptosis-inducing factor (AIF), AIF has been proposed by us as a candidate Ngb reductase. In this study, we tested this hypothesis and show that the Ngb-reductase activity of recombinant human AIF is negligible and hence incompatible with such a physiological function.